Teaching of Social Culture-Based Critical Literation for University Students - Nurita Bayu Kusmayati; Yeti Mulyati; Vismaia Sabariah Damaianti; Andoyo Sastromiharjo (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Critical literacy teaching aimed to improve students' ability to be literate about history, experience, language, and culture. In addition, students are able use their environment and culture code to compile reading text. Teaching critical literacy is done by building critical criticism generated through careful and critical assessment. Critical assessment aimed to obtain meaning from the writing and the intended meaning into writing. Critical literacy brings students to gain knowledge of social and cultural events. Teaching literacy is done through four stages which include (1) discrupting the commonplace, (2) interrogating multiple viewpoints, (3) focusing on the socio-political issues, and (4) taking actions.